PENERAPAN MEDIA PEMBELAJARAN PJOK PADA MASA PANDEMI COVID-19 (STUDI PTK PEMBELAJARAN BOLA BASKET PADA SISWA SMP) - Vina Hasna Shabrina, - (2021)
The purpose of this study was to determine the effect of using audio-visual media and student worksheets on the specific motion learning outcomes of basketball games in PJOK learning during the Covid-19 pandemic. This research method uses applied research. One of these studies uses a Classroom Action Research approach. The population of this research was carried out on the second grade students at SMP Negeri 12 Bandung. The sampling technique used is simple random sampling. Data collection techniques in this research was used google drive that has been provided. The instrument used in this research is an assessment rubric. The data analysis technique used in this research is instrument validity test, instrument reliability test, Class action research results and discussion results, it can be concluded that there is a significant influence from the application of audio-visual media equipped with student worksheets on game-specific motion learning outcomes. basketball. This is proven in every cycle and the action there is always a significant improvement in its implementation. The outcomes learning of this increase can be seen from the first cycle specific dribble motion with a percentage value of 59% in the second cycle an increase of 15% to 74%, specific motion passing from the first cycle with a percentage value of 57% in the second cycle an increase of 22% to 79%, shooting specific motion from the first cycle with a percentage value of 42% in the second cycle it increased by 2% to 44%.